2016
DOI: 10.1214/15-aop1055
|View full text |Cite
|
Sign up to set email alerts
|

Conformal weldings of random surfaces: SLE and the quantum gravity zipper

Abstract: We construct a conformal welding of two Liouville quantum gravity random surfaces and show that the interface between them is a random fractal curve called the Schramm-Loewner evolution (SLE), thereby resolving a variant of a conjecture of Peter Jones. We also demonstrate some surprising symmetries of this construction, which are consistent with the belief that (path-decorated) random planar maps have (SLEdecorated) Liouville quantum gravity as a scaling limit. We present several precise conjectures and open q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
395
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 201 publications
(403 citation statements)
references
References 95 publications
(184 reference statements)
5
395
2
1
Order By: Relevance
“…The boundary data for h is chosen so that the central ("north-going") curve shown should approximate an SLE 2 process (color figure online) the time-reversals of SLE κ (ρ) for all values of κ, a complete construction of trees of flow lines started from interior points, the first proof that conformal loop ensembles CLE κ are canonically defined when κ ∈ (4,8), and a geometric interpretation of these loop ensembles. In subsequent works, we expect these results to be useful to the theory of Liouville quantum gravity, allowing one to generalize the results about "conformal weldings" of random surfaces that appear [31], and to complete the program outlined in [32] for showing that discrete loop-decorated random surfaces have CLE-decorated Liouville quantum gravity as a scaling limit, at least in a certain topology. We will find that many basic SLE and CLE properties can be established more easily and in more generality using the theory developed here.…”
Section: η (T) = E I(h(η(t))/χ +θ)mentioning
confidence: 89%
See 4 more Smart Citations
“…The boundary data for h is chosen so that the central ("north-going") curve shown should approximate an SLE 2 process (color figure online) the time-reversals of SLE κ (ρ) for all values of κ, a complete construction of trees of flow lines started from interior points, the first proof that conformal loop ensembles CLE κ are canonically defined when κ ∈ (4,8), and a geometric interpretation of these loop ensembles. In subsequent works, we expect these results to be useful to the theory of Liouville quantum gravity, allowing one to generalize the results about "conformal weldings" of random surfaces that appear [31], and to complete the program outlined in [32] for showing that discrete loop-decorated random surfaces have CLE-decorated Liouville quantum gravity as a scaling limit, at least in a certain topology. We will find that many basic SLE and CLE properties can be established more easily and in more generality using the theory developed here.…”
Section: η (T) = E I(h(η(t))/χ +θ)mentioning
confidence: 89%
“…2,3,4,5). Several works in recent years have addressed special cases and variants of this question [6,8,10,19,28,31,37] and have shown that in certain circumstances there is a sense in which the paths are well-defined (and uniquely determined) by h, and are variants of the Schramm-Loewner evolution (SLE). In this article, we will focus on the case that z is point on the boundary of the domain where h is defined and establish a more general set of results.…”
Section: η (T) = E I(h(η(t))/χ +θ)mentioning
confidence: 99%
See 3 more Smart Citations